Plasmapheresis in Management of Oral Autoimmune Disorders - Gupta, Kanupriya (Journal of Drug Delivery and Therapeutics, 2019)
Systemic autoimmune diseases based on an immune pathogenesis produce autoantibodies and circulating immune complexes, which cause inflammation in the tissues of various organs. In most cases, these diseases have a bad prognosis without treatment. Autoimmune disorders are a group of poorly understood diseases in which the body fails to distinguish between self and non- self which could result in damage to the self. Oral mucous membrane may be affected by a variety of autoimmune mucocutaneous diseases such as pemphigus, bullous pemphigoid, mucous membrane pemphigoid, lichen planus, erythema multiforme, Steven Johnson syndrome, epidermolysis bullosa, linear IgA disease etc. These diseases (commonest being pemphigus) cannot be controlled in some cases, even with very high doses of systemic corticosteroids and immunosuppressive agents. In such cases plasmapheresis is one of the most effective therapeutic methods to deplete sera of immunoglobulin, including pathogenic autoantibodies. The aim of this review is to describe plasmapheresis as an adjunct therapy for oral autoimmune disorders. Keywords: autoimmune diseases, plasmapheresis, pemphigus, lichen planus, erythema multiforme, Steven Johnson syndrome, epidermolysis bullosa, linear IgA disease